Antibacterial Activity and Mode of Action of (+)-2,2'-Epicytoskyrin A - ANDRIA AGUSTA; DEWI WULANSARI; YULIASRI JAMAL; ARIEF NURKANTO; PRAPTIWI PRAPTIWI; AHMAD FATHONI (Indonesian Society for microbiology, 2015)
Antibacterial activity of (+)-2,2'-epicytoskyrin A, a main metabolite from culture of fungal endophyte Diaporthe sp. GNBP-10, was investigated against several strains of Gram-positive, Gram-negative bacteria, and one strain of Mycobacterium smegmatis. (+)-2,2'-Epicytoskyrin A exhibited prominent activity against Staphylococcus aureus BCC 1452 with minimum inhibitory concentration (MIC) value of 0.06 Î¼g mL-1. The effect of (+)-2,2'-epicytoskyrin A treatment to S. aureus, resulted in alteration of bacterial cell membrane with an increase of cation efflux, while the cytoplasmic content was not leaked out and finally resulted in cell damage.